Human iPS-derived pre-epicardial cells direct cardiomyocyte aggregation expansion and organization in vitro - Jun Jie Tan (Nature Portfolio, 2021)
The authors form pre-epicardial cells (PECs) from hiPSC-derived lateral plate mesoderm on treating with BMP4, RA and VEGF, and co-culture these PECs with cardiomyocytes, inducing cardiomyocyte aggregation, proliferation and network formation with more mature structures and improved beating/contractility.